MODEL PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) PADA MATERI KONTROVERSI (CONTROVERSY ISSUES) DI SEKOLAH MENENGAH PERTAMA (SMP) KOTA SEMARANG - Purnomo, Arif; Muntholib, Abdul; Amin, Syaiful (Jurnal Penelitian Pendidikan, 2016)
Social science subjects need to be constructed to shape the life of a democratic citizen. Organizing the material needed to form a controversy very intelligent character and critical learners. Organizing materials studied so interesting controversy will be able to develop a model that is capable of learning controversy develops the creativity of learners. The problems of this study are: (1) Which materials in IPS is controversial in the Junior High School?, (2) how teachers prepare and implement instructional materials IPS on the controversy?, and (3) how the teacher needs to be learning model on the IPS material controversy?.This study uses a design research and development (R & D), proceeded by a qualitative approach to determine the need for learning model IPS on the matter of controversy. Data collected through observation and interviews, and data analysis techniques used qualitative analysis.Based on the results of the study concluded that the learning material in the field of IPS controversy has not constructed well by the teacher. Teachers have not done the analysis of the material by separating the material which can be developed to foster critical thinking of students because it contains materials that controversy. Thus, the learning was done using a learning model that is not based matteri, because equating the controversy materials with other materials. This happens because the educational background of teachers who monodisiplin and analysis of materials that do not involve groups of teachers in the MGMP forum as well as a lack of understanding of the controversy in the learning material IPS. Based on the conclusions suggested: (1) teachers need to do the analysis of learning materials in MGMP so that the development of learning materials are made into more depth, and (2) there needs to be an understanding of the learning model that can be used by teachers to develop the material controversy in social studies.